«El Mapuzungun es naturaleza»: Estrategias didácticas para lenguas originarias desde las ciencias y el arte - Avendaño Caneo, Andrea (2020)
Elementary school can be the place where many children discover the world. Unfortunately, inside it school curricula suggest only one way of looking at the world. As a result, children’s current knowledge acquired in their home is not covered by teachers. This leads to cultural assimilation of children in schools that are housed in indigenous communities. For this work, I try to show how from the arts and natural sciences there is a commitment to develop counter-hegemonic activities that investigate the environment and claim the space of an original language. I will focus in activities developed in the South of Chile with Mapuche communities, where the connection of art, science and indigenous people initiates a better settling for schools. Finally, I will introduce allküntun (listening) as a way to understand basic knowledge in Mapuche culture.